Dementia Incidence, Burden and Cost of Care: A Filipino Community-Based Study - Dominguez, Jacqueline; Jiloca, Leo; Fowler, Krizelle Cleo; De Guzman, Ma. Fe; Dominguez-Awao, Jhozel Kim; Natividad, Boots; Domingo, Jeffrey; Dominguez, Jayvee Dyne; Reandelar, Macario; Ligsay, Antonio; Yu, Jeryl Ritzi; Aichele, Stephen; et al. (Frontiers in Public Health, 2021)
Background: In the midst of competing priorities and limited resources in low-middle-income countries (LMIC), convincing epidemiological evidence is critical for urging governments to develop national dementia plans. The majority of primary epidemiological studies on dementia are from high income countries (HIC). Implications for developing countries are typically extrapolated from these outcomes through modeling, meta-analyses, and systematic reviews. In this study, we directly assessed the incidence of dementia, disability adjusted life years (DALYs), and cost of care among community-dwelling Filipino elderly. Methods: This was a follow-up study of the prospective cohort Marikina Memory Ageing Project (MMAP). Baseline assessment was performed in 2011–2012, and follow-up was done in 2015–2016 (N = 748 at follow-up). Incident dementia was determined. Disease burden was computed using the incidence rates and DALYs. Both indirect and direct (medical and non-medical) costs of dementia care were computed. Results: The crude incidence rate was 16 (CI: 13–20) cases per 1,000 person-years (pyr) with 17 (CI: 12–21) per 1,000 pyr for females and 14 (CI: 9–21) per 1,000 pyr for males. Based on this incidence, we project an estimation of 220,632 new cases in 2030, 295,066 in 2040, and 378,461 in 2050. Disease burden was at 2,876 DALYsper 100,000 persons. The economic burden per patient was around Php 196,000 annually (i.e., 4,070 USD, or 36.7% of average family annual income in the Philippines). The majority (86.29%) of this care expense was indirect cost attributed to estimated lost potential earning of unpaid family caregivers whereas direct medical cost accounted for only 13.48%. Conclusions: We provide the first Filipino community-based data on the incidence of dementia, DALYs, and cost of care to reflect the epidemiologic and economic impact of disease. The findings of this study serve to guide the development of a national dementia plan.